Conduction drying of parboiled paddy in a screw conveyor heat exchanger - Obaldo, Leonard Ganir; Jindal, Vinod Kumar; Kim, Kong-Hwan; Exell, Robert H.B.; Mol, J.J.; Carl DuisDerg-Gesellschaft (CDG) Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1983)
An auger conveyor dryer tired by a rice husk was modified for drying parboiled paddy . Forty drying tests were employed to determine the individual and combined effects of experimental variables in relation to drying rate and milling quality of parboiled paddy. The rice husk furnace was e valuated based on rice husk teed rate and furnace draft . The simple and modified exponential models adequately represented the experimental data. However, the simple exponential. model fitted best as evidenced by its stronger sensitivity in showing the effects of agitation speed a nd t rough temperature . Both drying rate and milling quality were significantly influenced by auger speed , trough temperature and hold time while paddy fee d rate did not show any meaningful effect. Differences in the milling recovery of conducti on-dried , air-dried and s hade-dried paddy were not significant. Their corresponding head rice yields, however, were observed otherwise . Conduction-dried paddy indicated a relatively lower head rice yield compared to heated air-dried and shade tried paddy . However, further statistics confirmed that their head rice yields were comparatively equal at optimum operation of the conduction dryer. The percent breakage in the impact tester showed a direct correlation with percent head rice obtained from standard laboratory testing mill.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Rice, Parboiled